2010
DOI: 10.1007/s11284-010-0711-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial network structure and robustness of detritus‐based communities in a patchy environment

Abstract: The mechanisms that regulate the spatial distribution of species are an essential aid to understanding the effects of the environment on the persistence of populations and communities. The effects of spatial structure on the persistence and robustness of ecological communities can, in turn, prove useful in uncovering their functioning, e.g., in the decomposition of leaf detritus. We applied the framework of complex networks to evaluate the effects of spatial structure on the colonization process of leaf detrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
(52 reference statements)
1
17
0
Order By: Relevance
“…The structure of the co-occurrence network herein analysed, suggests a distribution of roles where only a few species are responsible for the metacommunity level connectivity. This pattern of role distribution [39] has also been described in a wide variety of biological networks including spatial [36,54], mutualistic [33,40,55], food web [35], genetic [34] and metabolic ones [39], supporting the commonality of this network structure. However, few studies have underscored the importance of biological attributes as determinants of species roles (but see [35,55]).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The structure of the co-occurrence network herein analysed, suggests a distribution of roles where only a few species are responsible for the metacommunity level connectivity. This pattern of role distribution [39] has also been described in a wide variety of biological networks including spatial [36,54], mutualistic [33,40,55], food web [35], genetic [34] and metabolic ones [39], supporting the commonality of this network structure. However, few studies have underscored the importance of biological attributes as determinants of species roles (but see [35,55]).…”
Section: Discussionsupporting
confidence: 57%
“…Modularity in ecological networks has increasingly been used to detect spatial aggregation of species in compartments of organisms sharing similar ecological attributes [33][34][35][36][37]. In co-occurrence networks, modules correspond to subsets of species whose probability of co-occurring across local communities is higher as compared with the probability of co-occurring with other species of the metacommunity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have detected compartments in food webs ( Krause et al, 2003 ) and pollinator networks ( Olesen et al, 2007 ). Bellisario et al (2010) found three distinct compartments in detritus-based macroinvertebrate communities inhabiting a fragmented network of salt ponds. Community compartments were associated with ponds in closer spatial proximity.…”
Section: Habitat Loss Triggers Instability Of Plant -Pollinator Netwomentioning
confidence: 99%
“…Since then, several metrics have been developed to identify modules and compartments (see Norberg 2007 andOlesen et al 2007 for a very brief treatment of this topic), but only after recent development of robust modularity-detecting algorithms (Newman andGirvan 2004, Guimer à andAmaral 2005) have modules and compartments been widely detected in ecological networks (Stouff er and Bascompte 2011, Dupont and Olesen 2012). Modularity has been identifi ed as a major structural property of ecological networks; it has been used to explore spatial structure in populations identifi ed by degree of genetic isolation (Fortuna et al 2009), colonization in metacommunities (Bellisario et al 2010), interaction networks (Olesen et al 2007, Rezende et al 2009), and biogeographical boundaries (Carstensen et al 2012). However, few studies have explored changes in modular structure in relation to spatio-temporal variability (Ramos-Jiliberto et al 2011, Dupont andOlesen 2012).…”
mentioning
confidence: 99%